Cost analysis of long-term outcomes of an urban mental health court. (October 2015) - Kubiak, Sheryl; Roddy, Juliette; Comartin, Erin; Tillander, Elizabeth
Highlights: MHC participants incurred substantial cost savings as a result of mental health court: total combined cost savings in the 12-month post-MHC period was 1, 417, 740. Those receiving the intervention incurred fewer costs in the outcome period than those in the comparison group; per person outcome costs range from 17, 113 to 39, 978. Unsuccessful Group members had higher prison incarceration than Successful or Compare Group members. Compare Group members had higher court, jail and residential substance abuse treatment costs than either of the treatment groups. No differences between groups in mental health treatment utilization during the outcome period. Abstract: Multiple studies have demonstrated decreased recidivism and increased treatment engagement for individuals with serious mental illness involved in Mental Health Courts (MHC). However, the limited availability of social and fiscal resources requires an analysis of the relationship between a program's effectiveness and its costs. Outcome costs associated with a sample of 105 participants discharged for more than 1 year – and grouped by completion status – were compared to an eligible sample not enrolled ( n = 45). Transactional costs analysis (TCA) was used to calculate outcomes associated with treatment, arrest, and confinement in the 12-month post-MHC. Total outcome costs for the Successful Group (16, 964) significantly differed from the Unsuccessful (32, 258) and Compare Groups (39, 870). Costs associated with the higher number of arrests for those in the Compare Group created the largest differences. Total cost savings between Successful and Compare ( M = 22, 906) equated to 916, 240 and savings between Unsuccessful and Compare ( M = 7612) were 494, 708. The total combined cost savings for participants in the 12-month post-MHC period was 1, 411, 020. While it is important to understand that MHCs and the individuals that they serve vary and these results are for a felony-level court, policy makers and researchers can use these results to guide their decision-making.